A Study to Assess the Effectiveness of a Structured Teaching Programme on the Level of Knowledge Regarding Primary Prevention of Oral Cancer Among Intermediate Students at Shatrughan Singh Inter College, Kalyanpur, Kanpur - Ratnanjali; Jyoti Singh; Naina Chaurasia; Neha Devi; Komal Pal; Kavita Gautam; Neha Pal; Mradul Saxena (International Journal of Oncological Nursing and Practices, 2025)
Background: Oral cancer is a significant public health concern, yet awareness of its causes, risk factors, and preventive measures remains low among adolescents and young adults. Since intermediate students have a limited understanding of oral cancer and its impact on health, the present study aimed to assess the effectiveness of an informational pamphlet in improving knowledge regarding the primary prevention of oral cancer. Method: A quantitative pre-experimental research design with a one-group pre-test and post-test approach was adopted. A sample of 30 intermediate students was selected using a convenient sampling technique. Data were collected using a structured, self-designed questionnaire focusing on knowledge of oral cancer risk factors, symptoms, and prevention strategies. Results: The findings revealed a significant improvement in knowledge following the intervention. The mean pre-test knowledge score was 67%, which increased to 96.7% in the post-test. In the post-test, 29 (96.7%) participants demonstrated an adequate level of knowledge, while 1 (3.3%) participant showed a moderate level. The paired t-test value (–12.0042, p<0.05) confirmed that the informational pamphlet was effective in enhancing awareness about the primary prevention of oral cancer. Furthermore, demographic factors such as age, gender, and monthly income were found to have a significant association with knowledge levels. Conclusion: The study concludes that health education through informational materials can effectively improve students’ awareness of oral cancer prevention. Integrating oral health education into the school curriculum could further reduce risk factors and promote long-term healthy behaviours.
Keywords: Awareness; Oral Cancer; Students; health education; prevention